2019
DOI: 10.2480/agrmet.d-18-00039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of air temperature and solar radiation on the occurrence of chalky rice grains in rice cultivars “Koshihikari” and “Akitakomachi”

Abstract: Global warming has already affected agricultural production worldwide. In Japan, the occurrence of chalky rice grains CRGs , which are low quality grains whose occurrence is exacerbated by high air temperature, has become a major issue. There is concern that this occurrence will become more frequent with increasing global warming; therefore, it is necessary to develop a model that can accurately estimate the impact of global warming on the occurrence of CRGs. In this study, such a model was developed for Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…However, it should be noted that the statistical relationships can be valid in different environments when models are calibrated using reliable and representative set of data for the conditions to be explored [40]. In the calibration process, the optimal duration after the flowering date for averaging air temperature differs among varieties [13,21]. The calibrated parameters, T crit and k , T represent quantitative characteristic of each variety for the occurrence of CRG [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that the statistical relationships can be valid in different environments when models are calibrated using reliable and representative set of data for the conditions to be explored [40]. In the calibration process, the optimal duration after the flowering date for averaging air temperature differs among varieties [13,21]. The calibrated parameters, T crit and k , T represent quantitative characteristic of each variety for the occurrence of CRG [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations and challenges in the model. The occurrence of CRG is known to depend on not only air temperature, but also radiation [21,41], wind speed [42], CO 2 concentration [43], and management, including nitrogen application [44] and planting density [45]. Although our simple model was accurate enough for estimating the occurrence of CRG under current conditions, it is an important challenge to develop and use a model that considers the other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bunyawanichakul et al, 2007;Franco et al, 2020) require engineering and process background, are completely isolated from the outside environment (i.e., do not consider the effect of pedo-climatic conditions) and are too sophisticated to be effectively coupled with rice models (consist of chains of interdependent differential equations that require huge number of input factors-variables and parameters-and measured data for calibration). Lastly, Takimoto, Masutomi, Tamura, Nitta, et al (2019) demonstrated that the simulation of chalky grains is more accurate when both air temperature and solar radiation are considered together and that low radiation levels can exacerbate the sensitivity of rice grains to temperature damage even in cultivars ranked as intermediate heat tolerant. This consideration is even more important in view of the models' application in a climate change impact assessment, since increasing air pollution and aerosol concentration are affecting the amount of solar radiation reaching the Earth's surface (Stanhill & Cohen, 2001;Thakur, 2018), causing the so called "global dimming" phenomenon.…”
Section: Cappelli and Bregagliomentioning
confidence: 99%
“…Rice, one of the world's major cereals, has a high incidence of low quality rice grains, called chalky rice grain (CRG; Fig. 1) as a result of high temperatures during the ripening period (Krishnan et al 2011;Masutomi et al 2015;Morita et al 2016;Takimoto et al 2019;Tashiro & Wardlaw 1991;Xiong et al 2017). CRG is fragile, which increases loss during milling, thus reducing the marketable yield (Bao 2019;Lyman et al 2013;Zhao & Fitzgerald 2013).…”
Section: Introductionmentioning
confidence: 99%